Durable Thin-Film DLC on Wafer Surfaces of Gravure Cylinders for Roll-to-Roll Printing of 1-Bit Electrodes and Microtext in Flexible Electronics and Graphic Security - Seetharamiahsrinivasaraju, Chandramohan (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.